Sistem Pendukung Keputusan dalam Pemilihan Sales Marketing Terbaik Menggunakan Simple Additive Weighting (SAW) Berbasis Website (Studi Kasus: PT. Citra Swarna Group (CSG) - Safii, Mochamad Yunaidi; Ardhianto, Eka (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
Citra Swarna Group is a company engaged in the property development sector and is rapidly developing in integrated real estate projects. However, in the process of giving appreciation, the company is considered unfair because the assessment is still subjective. Therefore this research will build a website-based decision support system in selecting the best sales marketing using the SAW method with assessment criteria such as number of sales, customer service, length of service, discipline, and attendance. Based on the research results, it was found that the best sales marketing ranking with the highest score was Khoirul Anam (A3) with a value of 0.949. The results of testing the SAW method on programs with manualization results show the same results and there is no difference. Based on the results of the research that has been done, there are suggestions for the development of further research, namely that it can be developed by adding more criteria so that research on sales marketing can be even more varied and can add presence features for sales marketing so there is no need to recapitulate the overall presence data.